Geology of the American Southwest : a journey through two billion years of plate-tectonic history - Baldridge, W. Scott (Cambridge New York Cambridge University Press, 2004)
"The processes of geology form our landscape over immeasurable expanses of time, and nowhere is this more self-evident than in the spectacular scenery of the Southwest of the United States of America. Two billion years of Earth history are represented in the rocks and landscape of this region, creating natural wonders such as the Grand Canyon, Monument valley, the Black Canyon of the Gunnison, and Death Valley." "Geology of the American Southwest provides the first concise and accessible account of the geology of the region. It relates local geological events to global plate tectonics, and documents complex episodes of sedimentation, mountain building and crust stretching, describing events leading to features of the modern landscape. Its broad chronological approach differs from other books about the geology of the region, which focus either on smaller regions, or are organized by travel route. This book will prove invaluable to students studying the geology of the southwest. It will also appeal to anyone interested in geology and landscape, and is a valuable guide for visitors to the National Parks of the region."--Jacket
Includes bibliographical references (p. [253]-276) and index.
84200
Keywords: Plate tectonics -- Southwest, New; Geology -- Southwest, New; Southwest, New